2009
DOI: 10.1016/j.jep.2009.04.047
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of propolis as a cariostatic agent and its actions on mutans group streptococci

Abstract: Propolis is a resinous substance made by bees. It possesses many biological activities, and many studies have reported its potential application in the control of dental caries. However, variability in the chemical composition of propolis is a potential problem in its quality control, especially since propolis has already been incorporated into products for oral use. Therefore, a critical analysis of the available data on propolis is warranted. The present review discusses the in vitro and in vivo studies publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 99 publications
2
84
0
9
Order By: Relevance
“…Greater scientific knowledge of the chemical composition of various types of propolis has helped envision their potential use and application in dental practice. 8,9,26,27 Previous studies have reported the strong antimicrobial activity of propolis against several bacteria of the oral m icrobiome, i ncludi ng S. mutans. 1,2,28,29,30,31 As confirmed in our study, propolis and some of its isolated compounds, such as apigenin and tt-farnesol, 11 have been found to display a major effect on microbial virulence (e.g., polysaccharide production and acid tolerance), rather than affecting unspecific or specific microbiome viability, considered a highly desirable quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater scientific knowledge of the chemical composition of various types of propolis has helped envision their potential use and application in dental practice. 8,9,26,27 Previous studies have reported the strong antimicrobial activity of propolis against several bacteria of the oral m icrobiome, i ncludi ng S. mutans. 1,2,28,29,30,31 As confirmed in our study, propolis and some of its isolated compounds, such as apigenin and tt-farnesol, 11 have been found to display a major effect on microbial virulence (e.g., polysaccharide production and acid tolerance), rather than affecting unspecific or specific microbiome viability, considered a highly desirable quality.…”
Section: Discussionmentioning
confidence: 99%
“…7 Among these, propolis is one such product that stands out for its biological properties, mainly as an antimicrobial, with direct application in dentistry. 8,9 Its anti-caries mechanism of action is associated with inhibition of glucosyltransferases and downregulation of specific genes associated with stress survival and tolerance in S. mutans. 10 Moreover, some flavonoids, terpenoids, isoflavones and other phenolic acids contained in propolis were found to diminish S. mutans acid production and tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride is available in a variety of dosage forms including sodium diamine fluoride (SDF), nanosilver fluoride (NSF), and propolis fluoride (PPF) [4][5][6][7][8][9][10][11][12][13][14]. Previous studies using SDF have shown that SDF consists of silver (Ag) and fluoride (F); silver acts as an antimicrobial agent and fluoride plays a role in enhancing remineralization as a strong anticaries agent [11].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, various biological properties have been demonstrated and attributed to different types of propolis, including antibacterial, antifungal, antiprotozoal, antioxidant, antitumor, anti-infl ammatory, anesthetic, wound healing, immunomodulatory, antiproliferative and anticariogenic activities (Dobrowolski et al, 1991;Ivanovska et al, 1995;Moura et al, 1999;Kujumgiev et al, 1999;Isla et al, 2001;Chen et al, 2004;Simões et al, 2004;Duran et al, 2006;Medic-Saric et al, 2009;Araujo et al, 2010;Sforcin, 2007;Libério et al, 2009;Pagliarone et al, 2009, Paulino et al, 2003.…”
Section: Introductionmentioning
confidence: 99%